Vibration control and shock absorption techniques for Hi-Tech manufacturing plants - Shih, Ming-Hsiang; Sung, Wen-Pei; Chen, Chang-Liang (The structural design of tall and special buildings, 2012)
SUMMARY The Hi‐Tech industrial plant that houses manufacturing processes of high precision requires much more vibration‐proof and earthquake‐proof structures than conventional plants. Taiwan is densely populated in limited space so that the Hi‐Tech industry does not have too much leeway for locating the manufacturing plant at locations that are away from sources of vibration. Hence, strengthening the capacity of Hi‐Tech plant structures to resist vibration is of primary importance to Hi‐Tech industries. In this research, the TFT‐LCD plant structure is selected for improving its shock absorption capability by replacing the braces at soft floor of the structure with Viscous Damper (VD) and Velocity and Displacement Hydraulic Damper (VDHD). The reinforced structure is then subject to vibrations of various accelerations for analysing the dynamics and efficiency of vibration reduction. The results show that: (1) When subject to micro vibration, VD and VDHD that have similar capabilities in controlling displacement and responding to acceleration are more effective than Buckling Resistant Bracing, BRB; (2) When subject to medium vibration, VD, BRB and VDHD show tremendous improvements in controlling the momentum of story drift or slab acceleration. However, BRB shows buckling that may lead to permanent structural deformation whereas the overflow occurs in the Relief valve of VDHD causing the energy‐dissipating viscosity of VDHD from a VD‐like to BRB‐like behavior; (3) Under strong vibration, when the maximum force of a VD exceeds its design value, the VD has inferior capacity than BRB and VDHD in reducing acceleration. The VDHD always has smaller acceleration response than BRB because the former has damping effect under strong vibration. The results obtained in this research will obtain the suitability of VDHD in reducing vibration and confirm its superior vibration reduction capability. Copyright © 2010 John Wiley & Sons, Ltd.